A Literature Review of Employee Theft - Santoso, Fajar; Artha, Bhenu; Fatimah, Rhamadinna; Shafa, Gefira Zahirah; Agustin, Safira Wulan (Relevance: Journal of Management and Business, 2025)
Employee theft is a common and significant problem in many businesses, especially in the hospitality sector where workers are frequently exposed to cash transactions, fixed assets, material presents, and consumable food and beverage items.  Because it deters investors and local businesses from operating in a particular area due to the possibility of their goods being stolen, this impacts local economic activity. This research provides a theoretical contribution to matters relating to employee theft, which can be used as a basis for further study. This research uses theoretical literature assessment, and a conceptual framework for further investigation is provided. Based on the conceptual research, the authors conclude that employee theft affects brand image and is affected by inconsistent auditing.